Design Trends in Fully Integrated 2.4 GHz CMOS SPDT Switches - Arif Sobhan Bhuiyan, Mohammad; Bin Ibne Reaz, Mamun; Jalil, Jubayer; Farzana Rahman, Labonnah; Gyu Chang, Tae (Current Nanoscience, 2014)
Fully integrated CMOS single pole double through (SPDT) Transmit/Receive (T/R) switch is an essential component of every compact transceiver for enabling sharing of a single antenna between its transmitter and receiver. The switch is expected to encompass very low insertion loss, relatively higher isolation with high power handling capability. But there is inevitable trade-off among the parameters of the switch which makes the design even more challenging at 2.4 GHz ISM band. This paper presents a bibliographical survey of the work published on improved performance of different switch topologies for 2.4 GHz ISM band transceiver applications. Different techniques reported in literatures for further improvements in the characteristics of CMOS switches are also highlighted. This review will serve as a comparative study and reference for the researchers in designing T/R switches for future 2.4 GHz ISM band applications.
Keywords: integrated